Staro - nové městské lázně - Kuric, Alexander (Vysoké učení technické v Brně. Fakulta architektury)
Předmětem studie je obnova areálu městských lázní v Brně-Zábrdovicích. Návrh počítá s obnovou lázeňského provozu ve stávající budově a s dostavbou objektu krytého bazénu. Zohledněny jsou při tom památková podstata stavby a technická specifika lázeňského provozu.

The subject of this study is the renovation of the city spa complex in Brno-Zábrdovice. The proposal presumes renewal of the old spa function and adds an indoor public pool as an expansion within the complex. The building's monument nature and specific technological requirements of the spa are also considered.
Old - new urban spa
Keywords: lázně; obnova; památka; Brno; Zábrdovice; Fuchs; spa; renovation; monument; Brno; Zábrdovice; Fuchs